Violence and power in the absence of tobacco control in prison environments - Alex Medeiros Kornalewski (Tobacco Induced Diseases, 2018)
It discusses the policy of controlling smoking in prisons, specifically regarding the legal gap that implies in the absence of public policies aimed at controlling tobacco and other drugs in these environments, on the grounds that these spaces are already under the norms of the Law No. 7,210, which establishes the Criminal Enforcement Act (LEP). Aims to reflect on the absence of tobacco control policies in prison institutions, specifically, those who are under the authority of the State. The methodological procedure is applied from a conceptual review of the effects of violence and power that allow the construction of this absence of smoking control in prisons, in addition to analyzing interviews of prisoners and security inspectors offered through projects already completed and news made available in the Observatory on the strategies of the Brazilian tobacco industry. In addition, we will use the process of analysis in which cases are seen as representation of the social, that is, the cases that will be discussed represent all the reports of the subjects that are in this intramural environment. The present communication offers some data: there is a consonance on the part of the individuals who inhabit the prison institutions regarding the problem of second-hand smoke, the consumption of cigarettes and other drugs proliferates or is potentialized within the prison and the disciplinary focus prevails, disregarding the issues in prisons.